Ruination and the William Jones Affair: Regenerative Debris and Contested Narratives in the Archives. Issue 1 (1st July 2021) - Canilao, Michael Armand P.
Abstract: This article uses the early twentieth-century Ilongot ethnographic fieldwork and the death of anthropologist William Jones in the Philippines as a vista into what the scholar of colonialism, Ann Stoler, refers to as ruination (Stoler 2013 ). I argue that the case of William Jones provides an important glimpse into colonial projects in two ways. First, it illustrates the intersection of anthropological expeditions and colonialism. Second, it argues that the colonial project itself produces archives, and in turn, colonial subjects through the making and reading of these archives. I argue for the use of incidental intelligence (Scott 1982 ) in navigating archival regenerative debris fields. Using archival data including court documents, fieldwork notes, and diaries, the article shows how colonial relationships are shaped, contested, and racialized. At the center of this process for the making of archives and the shaping of colonial subjects is Jones' fieldwork as well as "his people, " the Ilongots, who are romanticized headhunters.